GREEN TOURISM CONCEPT FOR RECOVERY INDONESIAN TOURISM MODEL AFTER PANDEMIC COVID-19 - Ika Sri Hastuti; Melaty Anggraini (SAMPURASUN, 2023)
Experiencing impact crisis, the number of tourists visiting Indonesia experience decreased, and had an impact on the occupancy of all hotels in Indonesia, which decreased by around 12.67% from the total in the previous year in 2019. A lot of energy work in the field of industry tourist experience bleaching consequence crisis that, recorded in the official site Kemenparekraf about 409 thousand power work housed. Adversity Industry tourist has implications for the inhibition developments in the sector others, such as continuity power work and business in the field of harmful tourism Indonesian economy. Research methods, the author uses qualitative research with scheme begins with determining the objectives or questions that underlie the research Destinations tour the could made example or model for repair quality tourist bulk previously in the post- pandemic era because already carry draft tourist sustainable. Customized with addition the rules more Health protocols tight in the pandemic era with pattern application CHSE (Cleanliness, Healthy, Safety, and Environmental Sustainability) certification recommended by World Health Organization (WHO) as a standard for implementing tourism side by side with COVID -19 so that people who can travel feel safe and trust that journey tour the no will caught transmission of the Covid-19 virus. Emergency response mechanisms that disable economic activity, including that which may come from the tourism industry. due to the fact that the existence of lockdowns and the prohibition of outside activities In houses makes activity tours halt Many have been stopped in order to stop the virus's inflow and outflow before it destroys the tourism industry's business model. Keywords: Tourism Strategy, Green Tourism, New Normal after pandemics